Mobile Learning: Utilization of Media to Increase Student Learning Outcomes - Edy Budiman; Sitti Nur Alam; Mohammad Aldrin Akbar (IAES Indonesia Section, 2018)
The low learning outcomes of students from year to year in the department of informatics in the course of data structure affect the learning outcomes. The purpose of this research is to know the difference between Student Learning Result between Using Mobile Media Learning application with Conventional Learning. Using a Quasi-Experimental Design. The sampling technique used is Cluster Purposive Sampling. Samples were divided into two groups: experimental groups taught using media mobile learning apps, and control groups taught using conventional learning. The test result data were tested using the Shapiro-Wilk test to know the data normality, F test for data homogeneity, and t-test to know the difference of learning result value with significant level (α = 0.05). Based on the data analysis result, a normality test result with the Shapiro-Wilk test obtained the value of both groups of samples is the normal distribution and the result of the F test is homogeneous. T-test result obtained by probability = 1.830 with α = 0.05 so probability value <α = 0.05 which means H0 is rejected, hence there is the difference of result of student learning between using application of Mobile learning media with conventional learning